Advancing Integrated Care through Psychiatric Workforce Development: A Systematic Review of Educational Interventions to Train Psychiatrists in Integrated Care. (August 2018) - Sunderji, Nadiya; Ion, Allyson; Huynh, Dan; Benassi, Paul; Ghavam-Rassoul, Abbas; Carvalhal, Adriana
Objective: Integrated or collaborative care is a well-evidenced and widely practiced approach to improve access to high-quality mental health care in primary care and other settings. Psychiatrists require preparation for this emerging type of practice, and such training is now mandatory for Canadian psychiatry residents. However, it is not known how best to mount such training, and in the absence of such knowledge, the quality of training across Canada has suffered. To guide integrated care education nationally, we conducted a systematic review of published and unpublished training programs. Method: We searched journal databases and web-based 'grey' literature and contacted all North American psychiatry residency programs known to provide integrated care training. We included educational interventions targeting practicing psychiatrists or psychiatry residents as learners. We critically appraised literature using the Medical Education Research Study Quality Instrument (MERSQI). We described the goals, content, and format of training, as well as outcomes categorized according to Kirkpatrick level of impact. Results: We included 9 published and 5 unpublished educational interventions. Studies were of low to moderate quality and reflected possible publication bias toward favourable outcomes. Programs commonly involved longitudinal clinical experiences for residents, mentoring networks for practicing physicians, or brief didactic experiences and were rarely oriented toward the most empirically supported models of integrated care. Implementation challenges were widespread. Conclusions: Similar to integrated care clinical interventions, integrated care training is important yet difficult to achieve. Educational initiatives could benefit from faculty development, quality improvement to synergistically improve care and training, and stronger evaluation. Systematic review registration number: PROSPERO 2014:CRD42014010295.